Molecular Docking Senyawa Bioaktif Tempuyung (Sonchus arvensis) Terhadap Reseptor ER-α Sebagai Inhibitor Kanker Payudara - Asaumi, Suci; Azra, Fajriah; Kusnanda, Arif Juliari (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Breast cancer is a disease characterized by uncontrolled cell growth and division in breast tissue, leading to lump formation. The enzyme ER-α (Estrogen Receptor Alpha) plays a significant role in breast cancer development. This study aims to investigate the potential of bioactive compounds from the tempuyung plant (Sonchus arvensis) to inhibit the ER-α enzyme (PDB ID: 3ERT) through in silico methods for breast cancer drug development. The bioactive compounds in tempuyung are potential ER-α inhibitors. Methods used include Lipinski’s rule prediction, pharmacokinetics and toxicity analysis, and molecular docking simulations using MOE software. Among 25 screened bioactive compounds, luteolin showed binding to the active site of ER-α with a binding affinity of -6.34 kcal/mol and an RMSD of 0.77 Å, interacting with amino acids Glu 353, Gly 521, and Leu 346. These findings suggest luteolin as a promising candidate for breast cancer treatment.